Effect of Health Insurance Policy on the Health Outcomes of the Middle-Aged and Elderly: Progress Toward Universal Health Coverage - Fan, Xiaojing; Su, Min; Zhao, Yaxin; Si, Yafei; Wang, Duolao (Frontiers in Public Health, 2022)
This population-based study aims to explore the effect of the integration of the Urban and Rural Residents’ Basic Medical Insurance (URRBMI) policy on the health outcomes of the middle-aged and elderly. A total of 13,360 participants in 2011 and 15,082 participants in 2018 were drawn from the China Health and Retirement Longitudinal Study. Health outcomes were evaluated using the prevalence of chronic diseases. A generalized linear mixed model was used to analyze the effect of the URRBMI policy on the prevalence of chronic disease. Prior to the introduction of the URRBMI policy, 67.09% of the rural participants and 73.00% of the urban participants had chronic diseases; after the policy’s implementation, 43.66% of the rural participants and 45.48% of the urban participants had chronic diseases. When adjusting for the confounding factors, the generalized linear mixed model showed that the risk of having a chronic disease decreased by 81% (odds ratio (OR) = 0.19; 95% confidence interval (CI): 0.16, 0.23) after the introduction of the policy in the urban participants; in the rural participants, the risk of having a chronic disease was 30% lower (OR = 0.70; 95% CI: 0.60, 0.82) than the risk in the urban participants before the policy and 84% lower (OR = 0.16; 95% CI: 0.14, 0.19) after the implementation of the policy; the differences in the ORs decreased from 0.30 prior to the policy to 0.03 after the policy had been introduced between rural and urban participants when adjusting for the influence of socioeconomic factors on chronic diseases. This study provides evidence of the positive effects of the URRBMI policy on improving the rural population’s health outcomes and reducing the gap in health outcomes between rural and urban populations, indicating that the implementation of the URRBMI policy has promoted the coverage of universal health.